A case study of the initial efforts to develop an innovative IT learning environment in a Singapore secondary school - Tan, Miiko Gibson. (2009)
This study sought to explore the initial efforts to bring about an IT innovation in a School. It also examined the change process, teacher readiness and the implications of national policies in IT use.